Parrhesia and form-of-life. Subjectivization and desubjectivization in Michel Foucault and Giorgio Agamben (Nóema, 2013)
In his recent books under the main title “Homo sacer”, Agamben focuses on the concept of form-of-life. With this article I provide an account of the meaning of this concept, arguing that its origins can be traced back to Foucaults “Lives of infamous men”.
Keywords: Agamben; Foucault; form-of-life; parrhesia; infamy